Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1515/geo-2018-0010
|View full text |Cite
|
Sign up to set email alerts
|

Umbrisols at Lower Altitudes, Case Study from Borská lowland (Slovakia)

Abstract: Umbrisols generally develop in a cool and humid climate. Therefore, occurrence of these soils in the Borská lowland of southwestern Slovakia is very uncommon, and this inspired the aim of this paper: Analysis of the natural conditions suitable for Umbrisol development. Umbrisols in the Borská lowland developed from aeolian quartz sands accumulated on Neogenne marine clay sediments. Their occurrence is connected with the groundwater table relatively close to the ground surface and this particularly determines U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This is in agreement with reports of other authors (Ganuza and Almendros 2003;Sanesi and Certini 2005;Dümig et al 2008;Läßiger et al 2008;Spaargaren 2008), who also showed that Umbrisols are relatively common in the mountains and highlands characterised by humid climate, biomass-rich vegetation and carbonate-free parent material. However, Umbrisols were also reported in the lowlands (Kristiansen and Greve 2003;OEwitoniak et al 2014;Jenèo et al 2018). Due to more strict criteria of the umbrik horizon implemented in the SGP6 (Kaba³a et al 2019), i.e.…”
Section: Discussionmentioning
confidence: 96%
“…This is in agreement with reports of other authors (Ganuza and Almendros 2003;Sanesi and Certini 2005;Dümig et al 2008;Läßiger et al 2008;Spaargaren 2008), who also showed that Umbrisols are relatively common in the mountains and highlands characterised by humid climate, biomass-rich vegetation and carbonate-free parent material. However, Umbrisols were also reported in the lowlands (Kristiansen and Greve 2003;OEwitoniak et al 2014;Jenèo et al 2018). Due to more strict criteria of the umbrik horizon implemented in the SGP6 (Kaba³a et al 2019), i.e.…”
Section: Discussionmentioning
confidence: 96%
“…In umbrisols, the water-logging process involves alternating oxidation and a reduction in soil caused by the seasonal rise and fall of groundwater, leading to the formation of Fe-Mn nodules or rust spots and other new bodies. This process is common in the umbrisols, with a high groundwater level in the valley plain, and is the main geochemical feature of umbrisol formation [43]. The Dongliaohe River valley plain has a long history of rice cultivation.…”
Section: Source Of Fe and Mnmentioning
confidence: 99%
“…The formation of umbric horizon is favoured by the carbonate-free bedrock and the climatic conditions occurring in the mountain areas (high amount of rainfall, low temperature). Therefore, this horizon is often identified in the soils of mountain areas (Balaceanu et al, 1987;Sanesi and Certini, 2005;Drewnik, 2008;Bedrna, 2009;Turrión et al, 2009;Bedrna et al, 2009Bedrna et al, , 2010Dlapa et al, 2010;Vasiliniuc et al, 2010;Chodorowski et al, 2012;Hudec and Hreško, 2013;Musielok et al, 2013Musielok et al, , 2019Barannyk, 2016;Jenčo et al, 2018). In soils of the Tatra Mts.…”
Section: Introductionmentioning
confidence: 99%